Auditors and Client Investment Efficiency - Bae, Gil Soo; Choi, Seung Uk; Dhaliwal, Dan S.; Lamoreaux, Phillip T. (The Accounting Review, 2017)
ABSTRACT This study examines the relation between auditors and their clients' investment efficiency. We hypothesize and find that auditor characteristics that proxy for an auditor's knowledge and resources are associated with higher client investment efficiency, after controlling for the auditor's effect on financial reporting quality. This result is consistent with auditors providing informational advantages to their clients in a generalized investment setting. We find that this auditor effect is more pronounced for clients who have a higher demand for information as measured by client size, industry competition, and client complexity. The effect is also more pronounced for clients of longer-tenured auditors. Overall, the results suggest that auditors may be one component to the management information environment and, as such, appear to influence capital investment behavior. JEL Classifications: M4; M42. Data Availability: All data are publicly available.